Analisis Marketing Channel Dan Penerimaan Usahatani Cabai Merah (Capsium Annum) Di Seluma - Triana Puspita; Yossie Yumiati; Rika Dwi Yulihartika (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The agricultural sector is one of the most important sectors in the Indonesian economy, particularly in horticultural commodities such as red chili (Capsicum annuum L.), which has high economic value and continuously increasing market demand. In Gunung Kembang Village, Semidang Alas Maras District, Seluma Regency, red chili farming is the main source of income for the community. However, the problem faced by farmers is the suboptimal selection of marketing channels that can maximize farm income. Therefore, this study was conducted to identify the patterns of marketing channels and the level of income earned by red chili farmers. This study aims to analyze marketing channels and the income of red chili farming. The method used is a quantitative descriptive method with a census technique involving 45 farmers as respondents. Data were collected through interviews, observations, and documentation, while the marketing channel analysis employed a descriptive method. Income analysis was calculated using the formula: Revenue = Production (Kg) × Selling Price (Rp). The results showed that there are three patterns of marketing channels: (1) producers directly to consumers at the farm, (2) producers directly to the market, and (3) producers to collectors, then to retailers, and finally to consumers. The most widely used marketing channel is the second channel, as it is considered more profitable and provides better selling prices for farmers. The total monthly revenue of red chili farming reached Rp29,048,335,000, with an average revenue per farmer of Rp645,518,556 per month.